The effectiveness of the self - efficacy enhancement program for village health volunteers in caring for patients with Diabetes Mellitus and Hypertension in community in Buriram Province - Ruanphet, kitipong; Saipech, Wasugree (Thai Journal of Nursing, 2024)
This quasi-experimental research aimed to evaluate the effectiveness of the self-efficacy enhancement program for village health volunteers in caring for patients with Diabetes Mellitus and Hypertension in community in Buriram Province. A sample of 66 village health volunteers, was purposively selected. They were equally divided into the experimental and control groups. Research tools included the self-efficacy enhancement program, a knowledge test, a self-efficacy questionnaire and a skill assessment in caring for patients with Diabetes Mellitus and Hypertension. Data were analyzed using descriptive statistics and t-test. The results of the study were as follows. After the experiment, village health volunteers in the experimental group gained significantly higher average score on knowledge, self-efficacy and skills in caring for patients with Diabetes Mellitus and Hypertension than before the experiment and the control group at p < .001.